Amplitude shift-keying demodulator circuit for bio-implantable micro-system stimulator - Hassoon, Mokhalad Khaleel (2016)
Recently there has been a lot of attention to the development of battery less implantable electronic devices for medical treatment and rehabilitation, these developments need to flexible high speed communication between the external equipment and implanted part. Nowadays, wireless power transfer (WPT) is used for transferring power and data to bio-implantable device. The main challenges in the design of biomedical implants circuits are data rate, size, power consumption and feasibility. In this thesis, proposes a new technique with the objective to overcome the above problems. Firstly, develop transcutaneous implantable telemetry system by design new structure of amplitude shift keying demodulator with low power consumption. Secondly, optimize and modify the geometries for inductive links based on the spiral circular coil, and testing and simulating the coil's performance on air. Thirdly, modifying efficient sub-electronic circuits for both the external and internal components. The modified rectifier and voltage regulator without a thermal protection circuit are designed in which passive elements are removed to generate adequate and stable 1.8 V DC. The new structure ASK demodulator is then designed based on voltage divider, small capacitor, one digital invertor to envelope signal and one cascade inverters to collect a synchronized demodulated signal data with minimum error, thereby no need to use comparator to extract the data and removing delay-locked loops (DLL) circuits for data synchronization. For this, professional Pspice 16.6 software is used to design the full system. The performance of the developed spiral circular coils is designed and simulated on air in lower frequency 6.78 MHz Industrial Scientific Medical (ISM) using the commercial HFSS 15.0 software. The system is operated at industrial scientific and medical (ISM) 6.78 MHz band with 12.5% modulation index to transfer data 500 Kb/s. The coupling efficiency between the two coils in the worst case is 68.77%, and for the optimum case is up to 74.47%. The transmitter and receiver coils used in the system offer 15 mm of distance transmission between coils. The gain surrounding coils is then simulated and plotted in the elevation and azimuthal planes. This demonstrates that the gain is constant and conforms to the omnidirectional pattern associated with such loop antennas. Furthermore, the driving application of the developed implanted micro-system can be used to stimulate nerves, muscle, implanted cochlear and may be also used for brain pacemaker implantation.